The impact of the crescent migration of Arabs to the Maghreb on the economic and social aspects - khelfat, kamel (Journal of Social Sciences and Humanities, 2020)
This study attempts to reveal the effects left by the crescent men who migrated to the Middle Maghreb, despite the exaggeration of many Orientalist and Arab studies on the devastation it has left on the economic and social structure, while we see that the jurisprudential texts have dealt with this phenomenon in some cases harsh and soft in some periods , Resulting in their integration into the social system of the Islamic Maghreb, and formed part of the Moroccan society revealed by many sources later. The tribes also negatively affected the construction of the Central Maghreb, especially in the early stages of migration from looting and banditry, and it was negatively reflected on the roads and commercial routes. Fear spread within the civil and rural communities, the impact of this on agriculture, and in that they took control of the suburbs, the countryside and the areas, which led to the gradual withdrawal of the barbarian population from them towards the fortified cities and taking shelter in the castles and mountains and settling in them, in addition to shrinking a lot of the lands of the inhabitants of the Central Maghreb, and they only had what was left in their hands The city walls and fortresses throughout the history of the Middle East in the Islamic Maghreb. This affected the economic and social life. These conditions helped the Hilal groups to settle and settle, and to re-establish commercial relations between the inhabitants of fortified cities, mountains, and Hilal groups. We note this through what was written in Journey Books and Geography about the parameters of stability and coexistence. Therefore, we saw that we address these events according to what the sources wrote, searching for the historical truth that was subjected to the ruin of economic cities, and coming up with fair results about semicircular migration.